The founding rate of venture capital firms in three European countries (1970–1990) - Manigart, Sophie (Journal of Business Venturing, 1994)
In this article, the sectorial and environmental forces that facilitate or inhibit the creation of venture capital companies are studied in the three European countries where the industry is most developed: the United Kingdom, France, and the Netherlands. The focus is on the start-up phase of the industry, the period from 1970–1990. The founding of firms can be studied on four different levels: entrepreneurial, organizational, population, and macroeconomic. In this study, a population approach is taken; this implies that we do not attempt to explain any single founding, but rather the aggregate number of foundings that occur in an industry in a certain period in a certain country. According to the organizational ecology theory, the population density (i.e., the total number of organizations in a population) is the major environmental factor that affects the founding rate through two processes. Initially, when the density is low, each founding eases new foundings, because the simple prevalence of a form tends to give it legitimacy (thereby spurring imitations), the training ground for qualified personnel grows and the supporting networks are widened and strengthened. The legitimation process does not grow forever: once enough organizations of a certain kind exist, legitimation attains a ceiling. As the number of organizations increases, the second process becomes dominant: the competition for resources (raw material, personnel, customers, capital) grows, leading to a negative relationship between the density and the founding rate, everything else being equal. Thus, the founding rate declines as the number of organizations increases, once a threshold is reached. The major hypothesis that is tested here is that the population density has an inverted U-shaped effect on the founding rate of venture capital organizations. In addition, the effect that the venture capital firms of the three countries have on each other is studied. Two populations are said to interact when the populations affect each other's growth rate, but the interaction need not be symmetrical. The second hypothesis, tested in this study, is that populations in different countries have a positive effect on each other and not a competitive effect because the legitimating effect does not halt at geographical borders. Yet, the competition for resources (capital, people, deals) among geographically different populations is limited in this industry. This study is valuable because until now, the existing ecological studies focus on long-established industries. Testing, the theory in a young industry that emerged only in the seventies (in Europe) has merits in its own right, because the technological progress after the Second World War has altered the organizational environment tremendously. The communication and transportation revolutions may have especially influenced the way in which organizations interact with each other and with the environment. The venture capital firms are furthermore special in the way they are organized with the dual structure of management company and investment fund(s). If the theory holds in this young industry, important additional evidence will be given that the theory is truly applicable to “populations of all types, in any time period, and in any society” (Carroll 1988, p. 18). Finally, this study extends the theory by giving evidence on how industries in different countries may interact upon each other. We show empirically that the major factor that influences the overall founding rate in each of the three countries is the density of the industry, i.e., the number of organizations that already exist in the industry; this confirms the population ecology theory. When the density is low, adding a new organization to the industry raises the probability of a subsequent founding; when the density is high, the contrary is true. The institutional changes considered here, such as the establishment of tax transparent legal entities or state guarantees against losses (in the Netherlands) and the establishment of secondary stock markets, do not significantly influence the founding rate in any of the three countries. Moreover, the Dutch foundings are positively influenced by the British density and the French foundings by the Dutch density; the British foundings are, on the contrary, negatively influenced by the Dutch density. The competitive effects between the Netherlands and the U.K. are thus more important than initially thought. The relationship between the density and the founding rate is the strongest, most consistent, and most significant relationship found in this study. Thus, the number of organizations that already exist in an industry is very important in explaining the founding of organizations, apart from, for example, the personality of the entrepreneur or from the networks in which he or she is involved. This indicates that, when trying to explain the founding of organizations, the industry structure, and more specifically the number of organizations that exist at the moment of the founding, cannot be ignored.